Volumetry Reality Augmented Reality Application with Android Based Marker Based Tracking Method (CESS (Journal of Computer Engineering, System and Science), 2022)
Volumetry reality is an application that implements AR with an android-based marker based tracking method for presenting spatial learning materials. Learning to build space and mathematics is still an obstacle in its presentation, delivery and understanding, and the Covid-19 pandemic has forced students to study independently. This encourages educational staff to innovate in providing learning media. Volumetry reality is built by applying AR technology with a marker based tracking method, in this case it is presented in the form of a handbook intended for elementary and junior high school levels. It is designed attractively and easy to use and is equipped with a calculator and mini quiz. Volumetry reality is built using unity and the Vuforia SDK (Software Development Kit). This application can be used by scanning and producing 3D objects up to a distance of 50cm and can be used in low light.
Keywords: Volumetry reality; AR; Vuforia; marker based tracking; Covid-19